2005
DOI: 10.1163/156856005774423944
|View full text |Cite
|
Sign up to set email alerts
|

Acid secretion in urinary bladder of rats subjected to gastrocystoplasty

Abstract: Urinary bladder augmentation with a segment of the stomach, i.e., gastrocystoplasty, has been used to improve capacity and compliance in patients with bladder dysfunction. In the present study, rats were subjected to gastrocystoplasty (using the oxyntic segment) with or without fundectomy (removal of the oxyntic part of stomach), and the acid secretion in the augmented bladder was measured. In freely fed rats, the pH values were neutral and not significantly decreased in the rats subjected to gastrocystoplasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In our previous study, we showed that the rats undergoing gastrocystoplasty with 90% fundectomy were capable of producing acid secretion in the bladder [20]. In the present study, we further showed that ECL cell hyperplasia and ECLoma developed in both the stomach and the segment of oxyntic mucosa after gastrocystoplasty with 90% fundectomy, but not after gastrocystoplasty with 10% fundectomy.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our previous study, we showed that the rats undergoing gastrocystoplasty with 90% fundectomy were capable of producing acid secretion in the bladder [20]. In the present study, we further showed that ECL cell hyperplasia and ECLoma developed in both the stomach and the segment of oxyntic mucosa after gastrocystoplasty with 90% fundectomy, but not after gastrocystoplasty with 10% fundectomy.…”
Section: Discussionsupporting
confidence: 66%
“…It has been shown that the transplanted oxyntic mucosa continues to function as stomach tissue [20,22], and antisecretagogues are recommended to treat low urinary pH levels [22]. This will, however, further potentiate the risk of developing carcinoids.…”
Section: Discussionmentioning
confidence: 99%